Hematologic changes after short term hypoxia in non-elite apnea divers under voluntary dry apnea conditions. - Ramona C Dolscheid-Pommerich (Public Library of Science (PLoS), 2020)
Purpose This study investigated the acute changes in full spectrum differential blood cell count including reticulocytes and immature reticulocytes after a voluntary maximal dry apnea in non-elite divers. Aim of the present study is to obtain information on important regulatory compensation mechanisms and to provide insights into apneic regulatory processes. Methods Ten apnea divers performed a voluntary dry mean apnea time of 317 sec [SD ±111 sec]. Differential blood cell count including reticulocytes was measured before and immediately after a single maximal breath-hold. To evaluate kinetics, blood samples were also taken after 30 min and 4 h. Value distributions are presented with dot plots. P-values were calculated using a mixed linear model for time dependency. Four difference values were compared to baseline values with Dunnett's procedure. Results Significant changes were found in red blood cell parameters for erythrocytes, red cell distribution width, hematocrit, hemoglobin, MCV, reticulocytes and immature reticulocytes, and in white blood cell parameters for leucocytes, lymphocytes, immature granulocytes, monocytes, basophile granulocytes, neutrophil granulocytes and eosinophil granulocytes and for thrombocytes. Conclusion Adaptive mechanisms regarding cell counts in elite apnea divers are not readily transferable to non-elite recreational sportspersons. Divers and physicians should be aware of the limited adaptive performance of humans in the case of extended apnea.